Theory of microbump antennas for conical radiation - Zhang, Yue Ping (2024)
Microbump antennas are a new class of antennas that are particularly suitable for antenna-on-chip solutions to silicon-based terahertz wireless systems. This article presents a theory of microbump antennas operating in the transverse magnetic (TM) modes for conical radiation. The theory is validated with a microbump antenna model scaled at 3 GHz. As expected, the theoretically calculated impedance and radiation characteristics closely agree with those measured and simulated results. The theory is applied to the analysis and design of a microbump antenna in a standard complementary metal-oxide-semiconductor (CMOS) process and a conventional bumping technology at 300 GHz. It is shown that the theory enables the accurate analysis and the efficient design of the microbump antenna. It is concluded that the microbump antenna outperforms the microstrip antenna at the expense of some increase in antenna height and fabrication step.